Realistic velocity profiles for wind-driven coastal currents - Young, Myron H.; Murray, Stephen P. (Mathematical modelling, 1987)
An accurate prediction of coastal current speed profile and direction has been a subject of interest. Witten and Thomas (1975) made a study based on a model with zero surface slope and a no-slip bottom condition. Murray and Young (1984) added surface slopes caused by wind stresses to this model. However, the no-slip condition does not necessarily agree with the real world. This paper proposes a model with a quadrtic bottom slip boundary condition according to Charnock (1959). The solution to the inhomogenous modified Bessel equation can no longer be solved explicitly. Two loops of iteration are required to obtain the solution. The outer loop iterates the surface slopes and the inner loop iterates the arbitrary constants, until the onshore current components are conserved. The results compare favorably to the constant eddy viscosity theory results and actual measurements.